Collective Bargaining in Ontario Public Hospitals - Kruger, Arthur (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1985)
This paper outlines and evaluates some of the more important developments that have taken place in the past three decades in Ontario public hospital labour relations.